A multi-scale modeling approach for UHMWPE composite laminates with application to low-velocity impact loading. (January 2022) - Staniszewski, Jeffrey M.; Boyd, Steven E.; Bogetti, Travis A.
Highlights: UHMWPE composite laminates are test under low velocity impact. Laminates are modeled using a multi-scale finite element approach. Testing and simulation are used to determine UHMWPE ply & delamination properties. Accurate predictions of peak back-face deflection and delamination extent are made. Abstract: Ultra-high molecular weight polyethylene (UHMWPE) composites are used in a wide array of protective armor systems. Design of these systems is largely performed through empirical studies which can be costly and time consuming. Modeling tools that enable enhanced performance through exploitation of the design of laminated composite architectures are desired. In this effort, we present a multi-scale, finite element-based representative volume element (RVE) approach that uses laminate mechanics to capture the ply-level material nonlinearity and strain-induced fiber reorientation of UHMWPE composite laminates subjected to low-velocity impact (LVI) loading. The effects of strain rate on the ply-level material response and predicted LVI response of UHMWPE composites are explored. An LVI methodology is developed to characterize the impact performance of thick-section UHMWPE composite materials and applied with the RVE finite element model to calibrate material and delamination properties for Honeywell® SpectraShield® II SR-3136 and DSM Dyneema® HB210. The multi-scale RVE approach accurately captures the peak back-face deformation and extent of delamination for laminates of these materials across three impact energies. The LVI methodology provides a means to evaluate and rank the impact performance of various UHMWPE composite materials, laminate architectures, and processing conditions. The LVI methodology coupled with the multi-scale RVE approach produces ply-level behavior and delamination properties linked to materials and processing conditions, ultimately creating a modeling tool that is capable of exploring the design of laminate architectures for UHMWPE composite structures.